2019
DOI: 10.1038/s41598-019-46739-y
|View full text |Cite
|
Sign up to set email alerts
|

QCT-based finite element prediction of pathologic fractures in proximal femora with metastatic lesions

Abstract: Predicting pathologic fractures in femora with metastatic lesions remains a clinical challenge. Currently used guidelines are inaccurate, especially to predict non-impeding fractures. This study evaluated the ability of a nonlinear quantitative computed tomography (QCT)-based homogenized voxel finite element (hvFE) model to predict patient-specific pathologic fractures. The hvFE model was generated highly automated from QCT images of human femora. The femora were previously loaded in a one-legged stance setup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Another important advantage is the availability of relatively fast and easy image-based model generation approaches. Such models have been used to predict bone strength [1][2][3], evaluate osteosynthesis- [4] and soft-tissue implants [5], investigate the effect of metastatic lesions on the bone's biomechanical behaviour [6,7] and many other subjects. Extensive research has been conducted to estimate the accuracy of FEM predicted bone behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important advantage is the availability of relatively fast and easy image-based model generation approaches. Such models have been used to predict bone strength [1][2][3], evaluate osteosynthesis- [4] and soft-tissue implants [5], investigate the effect of metastatic lesions on the bone's biomechanical behaviour [6,7] and many other subjects. Extensive research has been conducted to estimate the accuracy of FEM predicted bone behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation parameters like presence and amount of soft tissue, presence of other limbs or anatomical structures within the FOV, presence and location of a phantom and scanner settings are some major examples. The vast majority of published FE models of bone are based on human specimens scanned in vitro with soft tissue removed for easier handling or instrumentation [2,4,6]. CT scanning of isolated bone specimens does not only facilitate the image segmentation but also eliminates additional sources of error that are due to increased noise, streak artefacts, and beam hardening caused by the presence of other skeletal elements, implants or large amounts of soft tissue within the FOV.…”
Section: Introductionmentioning
confidence: 99%
“…assess the bone strength. Thus, finite element analysis (FEA) based on quantitative computed tomography (QCT) images can be a powerful tool for predicting fracture risk 17 . This technique provides an accurate determination of material properties, based on a volumetric measurement of bone density, and considers effective mechanical factors on bone strength 17 .…”
mentioning
confidence: 99%
“…Thus, finite element analysis (FEA) based on quantitative computed tomography (QCT) images can be a powerful tool for predicting fracture risk 17 . This technique provides an accurate determination of material properties, based on a volumetric measurement of bone density, and considers effective mechanical factors on bone strength 17 . Previous studies using the QCT-based FEA approach have reported promising results in predicting the strength of proximal femur 16 and vertebrae 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation